Analysis of different anti-interference system models based on discrete time Markov chain - Quan REN; Lei HE; Jiangxing WU (网络与信息安全学报)
Block chain,dissimilar redundancy and mimic defense technology have developed rapidly in different security fields of cyberspace.However,there is a lack of effective models to describe and analyze these three kinds of innovative technologies currently.The DTMC (discrete time Markov chain) was used to model and analyze the anti-interference of the three kinds of systems.The results show that mimic defense system which adopts dynamic heterogeneous redundancy architecture and negative feedback control mechanism can ensure the high availability of the system.The block chain system uses high redundancy consensus mechanism to have a higher anti-interference performance than mimic defense system and dissimilar redundancy system in a certain time,but its performance will decrease quickly after that.With the increase of redundancy,the anti-interference performance of the dissimilar redundancy system will tend to the high redundancy block chain rapidly.Compared with block chain,the anti-interference performance falling of dissimilar redundancy system will be relatively slower.